Study on the prediction of execution progress term considered the effect of climate - Hyok-Chol Kwak; Kwang-Il An (International Journal of Architecture and Urbanism, 2024)
The present time there are various problems by the complexity of building, the prediction of progress is difficult in execution progress management and the management of work is difficult ,the crash of work often cause and the cooperation in the field is difficult and the like. For this reason when we creat the progress schedule of execution it is important to find out the factor which influence on the progress date of execution and to predict the term on the basis of mathematic method. In many countries they find out the correct the progress term of execution by analysising the factor which influence on the progress term of execution. In this essay the correct progress term of execution is predicted from the statistical analysis about the climate condition which fit in with our actual conditions by mathematic method